Relatório de Estágio Profissional "Ensinar e Aprender em contexto de estágio: o percurso de uma estudante-estagiária" - Mariana Lopes Rocha (2019)
This report is part of the second cycle of studies aimed at the Master of Physical Education in Basic and Secondary Education, Faculty of Sports, University of Porto. This document is the end of a stage that is described by a preservice teacher who tried to think and describe all her experiences, learnings and results obtained over a school year. The school placement took place in a cluster of schools in the district of Aveiro, in a group composed by only one preservice teacher, the cooperating teacher and the faculty supervisor, at the academic year 2017/18. The preservice teacher was responsible for a tenth grade class of the Scientific-Humanistic Technological Sciences Course, as well as other teaching experiences, such as the first and second cycles of Basic Education. The document is organized in five chapters: the first is the introduction of this document; the second is about the personal dimension of the preservice teacher. The third one describes the framing of professional and institutional practice, describing and characterizing some aspects of the path which has been taken along the year. The fourth section describes the professional practice, which is divided in four areas, organization and management of teaching, assessment, the study carried out with the 6th grade class through the application of the personal and social responsibility model, and participation in school and the relationship with the school community; The last chapter presents the final considerations of this whole stage and some expectations for the future. Keyword: